The Effect of Administration and Supervision to Security of Local-Owned Assets - Jouzar Farouq Ishak; Tatik Sarinawati; Fitri Amaliyah; Kholifah Fil Ardhi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The security of local-owned assets is carried out with the aim that local-owned assets can be efficient and effective so that they can provide added value to all assets in the Provincial Government of West Java. In securing goods, an optimal administration and supervision system is needed to be a controller to reduce asset problems. This study was conducted to know the effect of the administration and supervision of local-owned assets on the security of local-owned assets. The research method used is a quantitative method. The data used is primary data in the form of a questionnaire which will be distributed to 17 regional organizations in the Provincial Government of West Java with 60 respondents. The sampling technique used is a non-probability sampling technique with a purposive sampling method. The results exhibit that administration, supervision, and security of local-owned assets are very strategic and vital functions. With the step of inventorying and revaluing local assets, it is hoped that it will be able to improve the administration of local-owned assets management so that the security of local-owned assets can improve people's welfare.